The systematic position of puzzling Sino-Himalayan Lophocolea sikkimensis (Lophocoleaceae, Marchantiophyta) is identified - Bakalin, Vadim A.; Maltseva, Yulia D.; Klimova, Ksenia G.; Nguyen, Van Sinh; Choi, Seung Se; Troitsky, Aleksey V. (PhytoKeys)
Lophocolea sikkimensis, a little-known Sino-Himalayan species, was collected in North Vietnam and its taxonomic position was identified by molecular genetic techniques. The species is characterized by generally narrowly pointed leaves, which are not seen in other representatives of Lophocoleaceae. We found that it belongs to the recently described genus Cryptolophocolea, although it is clearly morphologically dissimilar to other members of the genus. We propose a corresponding nomenclature combination: Cryptolophocolea sikkimensis comb. nov. This species is the only one in its genus with a predominantly Sino-Himalayan distribution; the vast majority of congeners are distributed in the Southern Hemisphere (mostly in Australasia). Reports of this species in Vietnam further confirm the close phytogeographic relationships of the flora of northern Indochina with those of the Sino-Himalayas and suggest that this species is found in other parts of the Hoang Lien Range and the southern Hengduan Range.